(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
A hermeneutic phenomenological analysis revealed that senior mental health practitioners experience their decisions as ’terrifying,’ ’weighty’ and ’painful,’ feeling exposed, under scrutiny. When imposing unwanted choices on others they claim they only do that which their role requires. A move towards inclusive decision-making is unlikely while practitioners promote fragile certainties.